2021
DOI: 10.1002/mana.201800420
|View full text |Cite
|
Sign up to set email alerts
|

On null‐controllability of the heat equation on infinite strips and control cost estimate

Abstract: We consider an infinite strip normalΩL=(0,2πL)d−1×R, d≥2, L>0, and study the control problem of the heat equation on ΩL with Dirichlet or Neumann boundary conditions, and control set ω⊂normalΩL. We provide a sufficient and necessary condition for null‐controllability in any positive time T>0, which is a geometric condition on the control set ω. This is referred to as “thickness with respect to ΩL” and implies that the set ω cannot be concentrated in a particular region of ΩL. We compare the thickness condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…• if M is the torus, a cube, or an infinite strip and H = −∆ is an appropriate self-adjoint realization of the Laplacian [9,5]; 16,4] (and [3] for a treatment of the partial harmonic oscillator); • if the domain M admits an appropriate covering and H is an operator such that every function in the range of the spectral projections satisfies a Bernstein-type inequality [7]. In the present paper we adapt Kovrijkine's approach to prove a spectral inequality for the Laplace-Beltrami operator on the sphere of radius R > 0, that is…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…• if M is the torus, a cube, or an infinite strip and H = −∆ is an appropriate self-adjoint realization of the Laplacian [9,5]; 16,4] (and [3] for a treatment of the partial harmonic oscillator); • if the domain M admits an appropriate covering and H is an operator such that every function in the range of the spectral projections satisfies a Bernstein-type inequality [7]. In the present paper we adapt Kovrijkine's approach to prove a spectral inequality for the Laplace-Beltrami operator on the sphere of radius R > 0, that is…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…As far as bounds on the control cost are concerned, one classically asks for the type of time dependency, which has been largely explored in [5,10,11,16,18,19,21,27], see also the references therein. However, the dependency of the control cost on geometric parameters of and has only recently been addressed in [6,7,9,19], see also [17] for previous results. Especially the work [19] focused on these dependencies, which have been exploited in several asymptotic regimes there in order to discuss homogenization.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…However, the considerations from [26] currently allow to apply this approach only in the case of Dirichlet boundary conditions. Remark 2.9 In the recent work [6], it has been shown that the system (2.1) on the strip 1 is null-controllable in any time 0 if and only if is a thick set (which can be arbitrarily changed outside the strip), and an explicit control cost bound has been provided.…”
Section: Letmentioning
confidence: 99%